Vonoprazan: A New Potassium-Competitive Acid Blocker. (June 2023) - St. Onge, Erin; Phillips, Bradley
Objective: To review the safety, efficacy, and tolerability of vonoprazan for the treatment of Helicobacter pylori infection in adults.Data Sources: A literature search was performed through PubMed using the following key terms: vonoprazan, Voquezna, TAK-438, potassium-competitive acid blocker, H pylori, and gastrointestinal.Study Selection and Data Extraction: Selected articles included those which described clinical studies of the pharmacology, pharmacokinetics, efficacy, safety, or tolerability of vonoprazan.Data Synthesis: Vonoprazan works by competing with potassium on the proton pump to inhibit gastric acid secretion. Phase 3 clinical trials have shown that vonoprazan is noninferior to proton pump inhibitors (PPIs) as a component of H pylori eradication regimens. Vonoprazan has also shown promise in duodenal ulcer-healing rates and in reducing symptoms of heartburn. Common adverse effects associated with vonoprazan include nasopharyngitis, diarrhea, constipation, flatulence, dyspepsia, headache, and abdominal pain.Conclusion: Clinical practice guidelines recommend PPIs as the antisecretory agent of choice in H pylori eradication regimens with histamine-2 receptor antagonists (H2RAs) as potential alternatives. However, the use of either class of medications may be limited by adverse effects, drug interactions, and tolerability. Potassium-competitive acid blockers (P-CABs), like vonoprazan, may be safe and effective alternative antisecretory agents for H pylori eradication regimens, as well as other gastrointestinal disorders.